1985
DOI: 10.1200/jco.1985.3.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Megestrol acetate therapy for advanced breast cancer.

Abstract: One hundred twenty-four patients with metastatic breast cancer were treated with 40 mg of megestrol acetate four times daily. Complete responses (CR) or partial responses (PR) were seen in 29 patients (23%). CR, PR, or stable disease (S) was seen in 80 patients (65%). The median duration of response was 22 months for CR and PR and ten months for S. A significantly higher response rate (CR + PR) was seen in estrogen-receptor-positive (ER-positive) patients (26%) and in patients who had not received prior therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…Trials using appetite stimulants, such as megesterol acetate, have shown an increase in adipose body weight. 7 Corticosteroids have been shown to improve appetite, food intake, well-being and performance status in a number of trials. 8 None of these studies showed any weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Trials using appetite stimulants, such as megesterol acetate, have shown an increase in adipose body weight. 7 Corticosteroids have been shown to improve appetite, food intake, well-being and performance status in a number of trials. 8 None of these studies showed any weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…increase in appetite and body weight in patients with breast cancer receiving MA at the usual dose (160 mg daily) has been noted as a collateral effect in up to 30% of patients ( 5 ) ; rapid weight gain and increase in appetite were observed when increasing the daily dose of the drug to 480 mg daily (6). Such an effect at different dose levels has been observed also with other gestagens (7).…”
mentioning
confidence: 57%
“…Unter Gestagentherapie kommt es vor allem zu einer deutlichen und von Patientinnen oft als unangenehm empfundenen Gewichtszunahme [13]. Gewichtszunahme und Ödembildungen werden unter Gestagentherapie weit häu-figer beschrieben als unter Anastrozoltherapie (Abb.…”
Section: Potentieller Schaden Der Gestageneunclassified